THE ABSENT YEARS OF ‘PO’ IN “KUNG FU PANDA 3” MOVIE: PSYCHOANALYTIC LITERARY CRITICISM - Polii, Andriy Joshua; Apollas, Kenzie Adam; Satriyo, Nathanael Raditya Putra (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2023)
This study aims at showing the correlation between the two early stages of childhood development of Po and the adult fixation that occurs at his present time; in addition, it is expected to give a deeper comprehensive understanding of how crucial the roles of parents in parenting during the childhood period. Having the data analyzed, a qualitative method was used to explain and describe the information collected which were related to psychological issues in the movie. The significant cinematography: camerawork in the movie, where the setting, plot, characters were described as the story is presented through moving pictures. Moreover, the theory of psychoanalysis: stages of psychosexual development by Sigmund Freud was used to explain the motives and behaviors of the character Po. As a result: 1) Po’s anxiety is triggered by his inadequate gratification of ‘id’ at the oral stage, making it difficult to control his dietary habit, pessimistic, dependent, and overly sensitive to rejection. 2) The lack of parenting at the anal stage makes him manifest a lack of self-control, disorganized, messy and careless behaviors. 3) Po eventually manages to gain his confidence; nevertheless, the adult fixation remains in him.